2015
DOI: 10.1080/03055698.2015.1043978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creating digital stories on foreign language education pre-service teachers’ TPACK self-confidence

Abstract: This study aimed to examine the effects of creating digital stories (DSs) on the self-confidence of foreign language education (FLE) pre-service teachers with regard to technological, pedagogical and content knowledge (TPACK). A onegroup pretest/posttest experimental research design was applied, supported by a qualitative approach. A total of 71 FLE pre-service teachers created DSs on a topic from the national foreign language programme. Data were collected through a self-confidence TPACK scale, demographic qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
4
18
0
1
Order By: Relevance
“…At the end of the process, the level of TPACK self-efficacy was improved in the courses where ICT was used. Sancar and Yanpar (2015) carried out a study to determine levels of self-confidence about TPACK amongst prospective teachers, and the participating teachers prepared digital stories in the course. Sancar and Yanpar (2015) stated that the preparation of digital stories in the course has improved the levels of selfconfidence about TPACK amongst prospective teachers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…At the end of the process, the level of TPACK self-efficacy was improved in the courses where ICT was used. Sancar and Yanpar (2015) carried out a study to determine levels of self-confidence about TPACK amongst prospective teachers, and the participating teachers prepared digital stories in the course. Sancar and Yanpar (2015) stated that the preparation of digital stories in the course has improved the levels of selfconfidence about TPACK amongst prospective teachers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was also observed in the study that the teachers working with the researchers who are information technologies teachers improved their TPACK competence. Previous research confirmed that a specific course focused on technology use helped foreign language teachers combine content, technology and pedagogy to produce better learning outcomes in the classroom (Kurt, Akyel, Kocoglu & Mishra, 2014;Sancar-Tokmak & Yanpar-Yelken, 2015). Content analyses concerning TPACK revealed that teachers from various branches also had similar experiences Yilmaz, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…In another research, the use of digital narration in open university system developed learners skills in many areas from motivation to collaborative working skill and helps their permanent (Yüzer and Kılınç, 2015). Digital storytelling process also increased pre-service teachers" self-confidence scores (Sancar-Tokmak and Yanpar-Yelken, 2015). Baki and Fevzioğlu (2017) analyzed the effects of digital stories on writing skills of 6 th graders and found that writing skills of the students increased after that process.…”
Section: Discussionmentioning
confidence: 99%